What Works Best When Building Partner Capacity and Under What Circumstances? - Paul, Christopher (RAND Corporation, 2013)
How can the U.S. Department of Defense increase the effectiveness of its efforts to help partners build the capacity of their military and other security forces? To form a base of evidence to inform policy discussions and investment decisions, a RAND study collected and compared 20 years of data on 29 historical case studies of U.S. involvement in building partner capacity.